Numerical Solution of MHD Casson Fluid Flow Due to a Moving Extensible Surface with Second-Order Velocity Slip and Carbon Nanotubes - SEETHI REDDY, Reddisekhar Reddy; POLU, Bala Anki Reddy (Engineering Transactions, 2018)
This theoretical research work deals with the effect of aligned magnetic field flow and heat transfer of carbon nanotubes towards a nonlinear stretching sheet. In addition, we have considered two kinds of carbon nanotubes, namely SWCNTs and MWCNTs, used with water as the base fluid. The governing boundary layer flow equations narrating partial differential equations are transformed into a system of ordinary differential equations with the assistance of similarity transformation. Obtained coupled non-linear differential equations are solved by fourth-order Runge-Kutta (R-K) method along with shooting technique. A comparative study of the formerly published results and the present results for a special case shows that all these results are in an excellent agreement.